The Birth of the Prophet Muhammad: Devotional Piety in Sunni Islam by Marion Holmes Katz (London and New York: Routledge, 2007. 275 pages) (American Journal of Islam and Society, 2009)
Despite the central importance of festival and devotional piety to premodernMuslims, book-length studies in this field have been relatively rare.Katz’s work, The Birth of the Prophet Muhammad, represents a tour-deforceof critical scholarship that advances the field significantly both throughits engagement with textual sources from the formative period to the presentand through its judicious use of theoretical tools to analyze this material. Asits title suggests, the work strives to explore how Muslims have alternativelypromoted and contested the commemoration of the Prophet’s birth atdifferent points in history, with a particular emphasis on how the devotionalistapproach, which was prominent in the pre-modern era, fell out of favoramong Middle Eastern Sunnis in the late twentieth century. Aimed primarilyat specialists in Middle Eastern and Islamic studies, especially scholarsof history, law, and religion, this work is recommended to anyone interestedin the history of Muslim ritual, the history of devotion to the Prophet, andthe interplay between normative and non-normative forms ofMuslim beliefand practice ...